Late Glacial to mid-Holocene palaeoclimate development of Southern Greece inferred from the sediment sequence of Lake Stymphalia (NE-Peloponnese) - Heymann, Christian; Nelle, Oliver; Dörfler, Walter; Zagana, Helen; Nowaczyk, Norbert R.; Xue, Jibin; Unkel, Ingmar (Quaternary international, 2013)
The sedimentary sequence of Lake Stymphalia (NE-Peloponnese) for the first time sheds light on the palaeoclimate development of Southern Greece from 15 to 5 ka BP. New geochemical data based on high-resolution X-ray fluorescence scanning provide in-situ, and continuous analysis of predefined element suites on split-core surfaces. Variations of elements over time were assessed constructing correlation matrices based on the calculation of Pearson correlation coefficients. The element suite includes Al, Si, K, Ca, Ti, Mn, Fe, Zn, Rb, Sr, and Zr. A major result includes that changes in element behaviour are related to hydrological changes in the catchment (precipitation), lake level status, and evaporation (insolation/solar activity), and are ultimately driven by climate. Major trends/shifts in elemental ratios correspond to the climate development in the Eastern Mediterranean region. Based on correlation of Rb/Sr, reflecting wet/dry climates, with foraminiferal proxies of marine core LC21 from the Southern Aegean Sea, and the stable oxygen-isotope record of Soreq cave (Israel), the Bølling-Allerød, the Younger Dryas, and the 8.2 ka cold event were identified.
Gesehen am 19.02.2025
Online veröffentlicht: 21. Februar 2013